2018
DOI: 10.1007/s11427-018-9333-1
|View full text |Cite
|
Sign up to set email alerts
|

A paradox: rapid evolution rates of germline-limited sequences are associated with conserved patterns of rearrangements in cryptic species of Chilodonella uncinata (Protista, Ciliophora)

Abstract: Some of the most extreme genome wide rearrangements are found in ciliates, which are unique in possessing both germline micronucleus and somatic macronucleus in every cell/organism. A series of DNA rearrangement events, including DNA elimination, chromosomal fragmentation, gene unscrambling and alternative processing, happen during macronuclear development. To assess the molecular evolution of macronuclear and germline-limited sequences in different cryptic species of Chilodonella uncinata, we characterized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Excision of IESs is generally not precise in Tetryhmena while must be precise in Paramecium , Chilodonella , Oxytricha and Euplotes . Moreover, gene scrambling is widespread in Oxytricha (Chen et al, ) and Chilodonella (Maurer‐Alcalá et al, ; Zhang, Wang, Katz, & Gao, ), but not frequently observed in Tetrahymena , Paramecium and Euplotes . As to the Euplotes in the present study, which is most closely related to Oxytricha based on morphology and phylogeny, its chromosomal fragmentation is similar to Oxytricha (Figure ); however, its DNA elimination resembles Paramecium (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Excision of IESs is generally not precise in Tetryhmena while must be precise in Paramecium , Chilodonella , Oxytricha and Euplotes . Moreover, gene scrambling is widespread in Oxytricha (Chen et al, ) and Chilodonella (Maurer‐Alcalá et al, ; Zhang, Wang, Katz, & Gao, ), but not frequently observed in Tetrahymena , Paramecium and Euplotes . As to the Euplotes in the present study, which is most closely related to Oxytricha based on morphology and phylogeny, its chromosomal fragmentation is similar to Oxytricha (Figure ); however, its DNA elimination resembles Paramecium (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Cyrtophorians are characterized by a glabrous dorsal side and prominent cytopharyngeal basket composed of a large number of microtubules (Lynn, 2008). Although several cyrtophorians have been studied recently (Chen et al, 2016;Pan et al, 2016;Zhang et al, 2018), the systematics of this group remains ambiguous. Therefore, the class TABLE 1 | Taxonomic schemes for the classification of 10 species ciliates in four systematic schemes.…”
Section: Introductionmentioning
confidence: 99%
“…2017; Wang, Chen, Sheng, Liu, & Gao, 2017;Wang, Zhang, et al, 2017;Xiong et al, 2016;Yan et al, 2018;Yan, Rogers, Gao, & Katz, 2017;Zhang, Wang, Katz, & Gao, 2018;Zhao, Wang, Wang, Liu, & Gao, 2017;Zhao, Yi, Warren, & Song, 2018). Although these topics have been studied for hundreds of years, there are still many unresolved issues, such as the considerable discordance between morphologies and molecules, which can be caused by convergent morphologies, cryptic species, plastic phenotypes or life-cycle stage variation (reviewed in Lahr, Laughinghouse, Oliverio, Gao, & Katz, 2014).…”
mentioning
confidence: 99%